Retrospektive: iDAI.werkstatt@dainst.de. Reflexionen aus der Ersten Arbeitswerkstatt zur Rekontextualisierung und Aufbereitung archäologischer Forschung mit iDAI.world-Systemen - Boecker, Velia; Burmeister, Therese; Moshfegh Nia, Shabnam; Watson, Juliane (Forum for Digital Archaeology and Infrastructure, 2021)
Many different projects work with the systems of the iDAI.world to digitally process and publish archaeological research and research data. Since 2018, the newly developed documentation system iDAI.field has been increasingly used to document new excavation projects or to process and (re)contextualize old excavations. In fall/winter 2020/2021, the first virtual workshop on »Recontextualization and Processing of Archaeological Research with iDAI.world-Systems« (original title: »Rekontextualisierung und Aufbereitung archäologischer Forschung mit iDAI.world-Systemen«) took place to provide an opportunity for exchange of experiences and discussion.